Ethico-legal issues in the medical profession : a case study of nursing profession in the world / Lateef Wale Adeyemo ... [et al.] - Adeyemo, Lateef Wale; Syahirah, Abdul Sukor; Amalina, Ahmad Tajudin; Ali Beltamer, Ali H (2015)
The paper analyses the professional rules and regulations that guide the nurse in carryout her professional duties. The paper discusses that the nurse should carrying out her duties diligently and carefully along with the doctrine of Islamic law by the way of fearing Almighty Allah; this is because of her closeness to patients in the hospitals and clinics.This paper identifies some actions, omissions, carelessness, negligent that can lead the nurse to a case in court or Shari‟ah court. Even if the affected patient can not afford litigation or remains silent over his right,some significant others like Human Rights Organizations, pressure groups can take up the case and make the affected Nurse to pay for such acts or omissions done against the victim. The paper elaborates some problem that may be caused by the nurse in the hospital due to her ignorant of law guiding her practice, pressure of work,or in a rare occasion, a lackadaisical attitude to others.The paper further explains the international/local/Islamic laws which regulate every aspect of communal life i.e the Nursing and Midwifery Regulation Acts that provide for the training, registration and discipline of Nurses and midwives as well as Shari‟ah principles guiding their professional ethic. This is because what one does some years back, if done today may put a Nurse in jail or make her pay heavy damages because the right to enforce one‟s denied fundamental human right has become a global issue and, of course ,has led to a new era in the act of caring for patient. In addition the finding in the paper will be a good guidance to medical officers,Islamic jurists, academicians scholars, researchers throughout the world as patient/medical officer relations in the hospital become a fundamental human right issue before the World Health Organization.